The Effect of the Jigsaw Learning Model in Animal Tissue and Body Structure Courses on Student Problem Solving Ability - Mulya Fitrah Juniawan; Wiwi Wikanta; Asy'ari Asy'ari (Postgraduate, University of Mataram, 2023)
This study aims to find out how students' problem-solving skills in the subject of animal body tissue and structure use the Jigsaw learning model. This type of research is quantitative research with a sample size of 70 students of the biology education study program. The research sample was taken from students who were normally distributed, had the same characteristics (homogeneous), and had the same average value. The data analysis technique uses simple linear regression. The results showed that there was a significant influence between the Jigsaw cooperative learning model in the animal tissue and body structure course on the problem-solving abilities of students in the biology education study program with a significance value of 0.000 <0.05, so that the jigsaw learning model can help students improve problem-solving skills